(untitled) (The Journal of Plant Protection Sciences, 2022)
Worldwide sustainability of agriculture suffers a designated by the EPA to be a “reduced-risk” severe setback arising from the use of chemical pesticide and is considered an organophosphate pesticides on living systems and the replacement (7). Bioassays of Indoxacarb environment. The use of organophosphates and showed that ingesting Indoxacarb was highly chlorinated insecticides pose problems, such as toxic to third instars of lepidopteron larvae in poisoning in man and other animals (22), pest course of exposure between 2 to 5 days (23).